2023
DOI: 10.1038/s41598-023-28653-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the correlation of the pan-cancer gene HAUS5 with prognosis and immune infiltration in liver cancer

Abstract: Liver hepatocellular carcinoma (LIHC) is one of the most common malignancies and places a heavy burden on patients worldwide. HAUS augmin-like complex subunit 5 (HAUS5) is involved in the occurrence and development of various cancers. However, the functional role and significance of HAUS5 in LIHC remain unclear. The Cancer Genome Atlas (TCGA), Genotype-Tissue Expression (GTEx), Cancer Cell Line Encyclopedia (CCLE) and Gene Expression Omnibus (GEO) databases were used to analyze the mRNA expression of HAUS5. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…PANoptosis is defined as a unique inflammatory programmed cell death pathway that is driven by caspases and receptor-interacting protein kinases (RIPKs) and regulated by multiprotein PANoptosome complexes 23,24 . PANoptosis plays a significant role in tumor treatment 25,26 , as this form of inflammatory cell death leads to the release of inflammatory signaling molecules and intracellular tumor antigens, triggering a robust immune response 27,28 . Research has revealed that ZBP1 is a key upstream regulator of PANoptosis 19,29,30 .…”
mentioning
confidence: 99%
“…PANoptosis is defined as a unique inflammatory programmed cell death pathway that is driven by caspases and receptor-interacting protein kinases (RIPKs) and regulated by multiprotein PANoptosome complexes 23,24 . PANoptosis plays a significant role in tumor treatment 25,26 , as this form of inflammatory cell death leads to the release of inflammatory signaling molecules and intracellular tumor antigens, triggering a robust immune response 27,28 . Research has revealed that ZBP1 is a key upstream regulator of PANoptosis 19,29,30 .…”
mentioning
confidence: 99%